Multiagent coordination enabling autonomous logistics - Schuldt, Arne; SpringerLink (Online service). (Berlin Springer, 2011)
This book describes the implementation of autonomous control with multiagent technology. Therewith, it tackles the challenges of supply network management caused by the complexity, the dynamics, and the distribution of logistics processes. The paradigm of autonomous logistics reduces the computational complexity and copes with the dynamics locally by delegating process control to the participating objects. As an example, shipping containers may themselves plan and schedule their way through logistics networks in accordance with objectives imposed by their owners. The technologies enabling autonomous logistics are thoroughly described and reviewed. The presented solution has been used in a realistic simulation of real-world container logistics processes. The validation shows that autonomous control is feasible and that it outperforms the previous centralised dispatching approach by significantly increasing the resource utilisation efficiency. Moreover, the multiagent system relieves human dispatchers from dealing with standard cases, giving them more time to solve exceptional cases appropriately.
Part I Logistics Requirements -- Introduction -- Supply Network Management -- Autonomous Control in Logistics -- Part II Multiagent-Based Approach -- Agent Technology -- Potential for Cooperation in Autonomous Logistics -- Team Formation in Autonomous Logistics -- Team Action in Autonomous Logistics -- Part III Application and Evaluation -- Implementing Autonomous Logistics -- A Case Study in Container Logistics -- Transition to Autonomous Logistics -- Conclusion and Outlook -- Index.
Electronic reproduction.
Keywords: Automatic control; Multiagent systems; Business logistics; Electronic books